Uji Efektivitas Antibiotik Ekstrak Daun Kayu Manis (Cinnamomum Burmannii) Terhadap Pertumbuhan Bakteri Salmonella Typhi Secara In Vitro - Lestari Safitri; Yenita Yenita (ANATOMICA MEDICAL JOURNAL | AMJ, 2020)
IIntroduction: Salmonella typhi is a rod-shaped or bacillus, gram negative, facultative anaerobic, moves with peritric flagella, and it doesn’t produce spores. Salmonella is pathogenic for humans or animals if obtained from the oral route. Cinnamon leaf (Cinnamomum burmannii) has antibiotic effect on bacteria. Flavonnoid, saponin, alkaloid, and tannin on cinnamon leaves is known to inhibit Salmonella typhi bacteria. Methodology: This study used an experimental method. The technique used in measuring antibiotic activity is the method of disk diffusion. Result: The result of the research showed that cinnamon leaf extract (Cinnamomum burmannii) with concentration of 80%, 40%, 20%, and 10% yielded average of clear zone diameter 17,863 mm, 13,692 mm, 10,352 mm, and 9.79 mm. While the diameter of the clear zone of chloramphenicol is 19.72 mm and the aquadest is not obtained clear zone. Conclusion: Cinnamon leaf extract with 80% concentration has the highest clear zone in the treatment groupKeywords: Salmonella typhi, cinnamon leaf extract